Comparative analysis of absent in melanoma 2-inflammasome activation in Francisella tularensis and Francisella novicida - Alqahtani, Maha; Ma, Zhuo; Miller, Jacob; Yu, Jen; Malik, Meenakshi; Bakshi, Chandra Shekhar (Frontiers in Microbiology, 2023)
Francisella tularensis is a highly virulent Gram-negative bacterium that causes the fatal zoonotic disease tularemia. The mechanisms and signaling pathways leading to the absent in melanoma 2 (Aim2) inflammasome activation have been elegantly elucidated using Francisella novicida as a model. Although not pathogenic for humans, F. novicida can cause tularemia in mice, and the inflammatory response it triggers is the polar opposite to that observed in mice infected with F. tularensis strains. This study aimed to understand the mechanisms of Aim2 inflammasome activation in F. tularensis-infected macrophages. The results reveal that macrophages infected with the F. tularensis live vaccine strain (LVS) induce lower levels of Aim2-dependent IL-1β than those infected with F. novicida. The suppression/weak activation of Aim2 in F. tularensis LVS-infected macrophages is due to the suppression of the cGAS-STING DNA-sensing pathway. Furthermore, the introduction of exogenous F. tularensis LVS DNA into the cytosol of the F. tularensis LVS-infected macrophages, alone or in conjunction with a priming signal, failed to restore IL-1β levels similar to those observed for F. novicida-infected macrophages. These results indicated that, in addition to the bacterial DNA, DNA from some other sources, specifically from the damaged mitochondria, might contribute to the robust Aim2-dependent IL-1β levels observed in F. novicida-infected macrophages. The results indicate that F. tularensis LVS induces mitophagy that may potentially prevent the leakage of mitochondrial DNA and the subsequent activation of the Aim2 inflammasome. Collectively, this study demonstrates that the mechanisms of Aim2 inflammasome activation established for F. novicida are not operative in F. tularensis.